2022
DOI: 10.1073/pnas.2201879119
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-pair spin signatures from macroscopically aligned heteroacenes in an oriented single crystal

Abstract: The photo-driven process of singlet fission generates coupled triplet pairs (TT) with fundamentally intriguing and potentially useful properties. The quintet 5 TT 0 sublevel is particularly interesting for quantum information because it is highly entangled, is addressable with microwave pulses, and could be detected using optical techniques. Previous theoretical work on a model Hamiltonian and nonadiabatic transition theory, called the JDE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 56 publications
5
36
0
Order By: Relevance
“…According to the JDE model, the 5 (TT) 0 quintet state of chromophore dimers can be generated as a nearly pure quantum state by making the exchange interaction between two chromophores sufficiently large and by making the principal axes of the two chromophores parallel to each other and to the Zeeman field 19 . This model has explained well the experimental results of oriented crystalline samples 20 , 21 . To date, the spin aspect of SF has only been used to explain the microscopic mechanisms of SF.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to the JDE model, the 5 (TT) 0 quintet state of chromophore dimers can be generated as a nearly pure quantum state by making the exchange interaction between two chromophores sufficiently large and by making the principal axes of the two chromophores parallel to each other and to the Zeeman field 19 . This model has explained well the experimental results of oriented crystalline samples 20 , 21 . To date, the spin aspect of SF has only been used to explain the microscopic mechanisms of SF.…”
Section: Introductionsupporting
confidence: 82%
“…There was an approximate correlation between ESR and DNP profiles, confirming that DNP was performed using triplets and quintets, respectively. Although triplet gave the larger DNP effect than quintet in the present system, it is possible to suppress the formation of triplet by selectively synthesizing dimers, and it would be possible to improve the quintet DNP performance more by selectively generating 5 (TT) 0 among the quintet sublevels by controlling the orientation of the dimers relative to the magnetic field 21 . These results indicate that nuclear hyperpolarization of water molecules was successfully achieved using SF-derived quintet electron polarization.…”
Section: Resultsmentioning
confidence: 91%
“…Future work will compare the relative merits between the two types of experiments. Notably, there are two recent works in the literature that use singlet fission in the pursuit of quantum information applications, but with chromophores in crystals that are oriented in the field, not dimers 8 , 32 . The value of T 2 for TIPS-BP1' dimers reported here at 75 K is similar to that reported in ref.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in solid-state SF systems, individual chromophores are aligned through crystallization. Triplet pairs may form at sites where J is large, but in crystals the excitons are mobile and hopping unpairs the biexciton state, which can then decohere 8 12 . There have been no reports of an aligned system of molecular SF dimers, where chromophores are covalently coupled through synthetic design.…”
Section: Introductionmentioning
confidence: 99%
“…Singlet fission (SF) is a multiexciton generation process wherein a singlet excited state on one chromophore, S 1 , partitions its energy with a nearby chromophore in its ground state, S 0 , to generate two triplet excited states, T 1 + T 1 . As a downconversion process, SF can be used in photovoltaics to reduce thermalization losses, but recent work has also suggested that intermediate triplet-pair states, particularly 5 TT, may have quantum information (QI) applications, since these may form with high initial spin polarization. Distinct pair states, n TT, form when two adjacent triplet states experience a strong interchromophore exchange interaction, such that pairs with different spin multiplicities, n = 1, 3, or 5, possess different energies.…”
mentioning
confidence: 99%